Detection of the amount of residue degradation rate of six commonly used insecticides in cauliflower under supervised field trial - Ahmed, Md Sultan; Ali Sardar, Md Mohsin; Ahmad, Masum; Kabir, Kamal Humayun (Asian-Australasian Journal of Food Safety and Security, 2018)
The present study was made to detect the amount of residue degradation rate of insecticides in cauliflower under supervised field trial. Six field trials were carried out sprayed with recommended dose of acephate (2 g/L of water), cypermethrin (1 ml/L of water) and diazinon, malathion, quinalphos and fenitrothion (2 ml/L of water of each), respectively. Samples were collected at 0, 1, 3, 5, 7, 10 and 15 days after spray (DAS). The degradation rate of cypermethrin, diazinon, quinalphos and fenitrothion were detected up to 10 days after spray (DAS) in cauliflower, while malathion and acephate could be detected at 5 and 15 DAS respectively. The detected quantities were above Maximum Residue Limit (MRL) up to 7 DAS for quinalphos, Fenitrothion and acephate, 5 DAS for diazinon and cypermethrin and 3 DAS for malathion. Malathion degraded quickly and acephate degraded slowly as compared to other tested insecticides. Therefore, malathion might be use for cauliflower cultivation having waiting period of 5 DAS and incase of diazinon and cypermethrin it was 7 DAS. Quinalphos, fenitrothion and acehate had higher waiting period of 10 DAS which might be due to slower rate of degradation. Asian Australas. J. Food Saf. Secur. 2018, 2(2), 109-114